2022
DOI: 10.1002/cnm.3639
|View full text |Cite
|
Sign up to set email alerts
|

Automated generation of 0D and 1D reduced‐order models of patient‐specific blood flow

Abstract: Three-dimensional (3D) cardiovascular fluid dynamics simulations typically require hours to days of computing time on a high-performance computing cluster.One-dimensional (1D) and lumped-parameter zero-dimensional (0D) models show great promise for accurately predicting blood bulk flow and pressure waveforms with only a fraction of the cost. They can also accelerate uncertainty quantification, optimization, and design parameterization studies. Despite several prior studies generating 1D and 0D models and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 115 publications
0
18
0
1
Order By: Relevance
“…Anatomic Model Generation 3D geometries of patient-specific aortas were generated by importing the MRI magnitude images into SimVascular and manually segmenting the vessels. Centerlines were automatically extracted from the 3D geometry to create the 0D model comprising a network of lumped parameter elements (resistors, capacitors and inductors) [5]. The 3D volume was discretized using a mesh of tetrahedral elements.…”
Section: Cfd Fsi Simulationmentioning
confidence: 99%
“…Anatomic Model Generation 3D geometries of patient-specific aortas were generated by importing the MRI magnitude images into SimVascular and manually segmenting the vessels. Centerlines were automatically extracted from the 3D geometry to create the 0D model comprising a network of lumped parameter elements (resistors, capacitors and inductors) [5]. The 3D volume was discretized using a mesh of tetrahedral elements.…”
Section: Cfd Fsi Simulationmentioning
confidence: 99%
“…To create the 0D models, the vessel's centerlines and cross-sectional areas were automatically extracted from the 3D models [23]. Vessel junctions (bifurcations) were then automatically identified and the centerline network was split into branches and junctions.…”
Section: D Model Constructionmentioning
confidence: 99%
“…0D models are comprised of lumped-parameter elements such as resistors, capacitors, and inductors that connect to form an entire network. Previous work by Pfaller et al demonstrated the robustness of 0D models by comparing to 3D results in 72 patient-specific cardiovascular models [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already shown that, in general, one-dimensional (1D) modeling coupled with lumped-parameter, zero-dimensional (0D) models, derived from full threedimensional (3D) models by means of simplifying assumptions about flow, structure, and their interaction, is sufficient to obtain realistic and accurate numerical results, particularly when the flow is predominantly unidirectional [46,33,44]. Moreover, in contrast to 3D simulations with prohibitively high computational costs, 1D models allow for the investigation of the hemodynamics of the entire main circulatory system [1,31,34].…”
Section: Introductionmentioning
confidence: 99%